Crambe fruit drying with natural air in stationary dryers - Cardoso Neto, Sebastião; Resende, Osvaldo; Costa, Lilian; Oliveira, Daniel Emanuel (Revista Ciência Agronômica, 2018)
The aim of this study was to assess the drying behavior and quality of crambe fruit seeds dried with natural air and submitted to different airflows in stationary dryers. Dryings were carried out in July and September 2014. The experiment consisted of three treatments of drying the crambe fruits with natural air in stationary dryers with airflows of 10.08, 15.05, and 25.03 m3 min−1 t−1 and a control treatment composed of crambe fruits with an initial moisture content without going through the drying process. After drying, tests of moisture content, germination, germination rate index, and electrical conductivity were performed in order to compare the treatments. The data were submitted to analysis of variance and mean comparison by the Tukey’s test at 5% significance. Among the airflows used in the experiment in both natural air dryings in July and September, no interference was observed for crambe fruit quality. Drying carried out in September was faster and showed a lower expenditure and cost of electricity when compared to that performed in July, which is due to better climatic conditions. No difference was observed in the drying times between airflows, but the drying with natural air using an airflow of 15.05 m3 min−1 t−1 was more profitable.